Choledochal Malformations: The Scottish Experience - Yeung, Baldwin Po Man; Broadis, Emily; Maguire, Kirsty; Bradnock, Timothy J.; Munro, Fraser D.; Driver, Chris P.; Haddock, Graham (European Journal of Pediatric Surgery, 2012)
Introduction Excisional surgery for choledochal malformations in Scotland is currently performed in three specialist pediatric surgical centers using open or laparoscopic-assisted techniques. We reviewed the outcome of children who had excisional surgery in Scotland between 1992 and 2010.Materials and Methods Case notes for all patients undergoing excisional surgery in any of the three specialist pediatric surgical centers in Scotland between 1992 and 2010 were retrospectively reviewed.Results A total of 25 patients were identified, with a female preponderance of 4:1. Of these, three patients (12%) were diagnosed by antenatal ultrasound scan. The commonest presenting symptoms were anorexia (56%), abdominal pain (52%), and jaundice (52%). Only 20% had the classical triad of abdominal pain, jaundice, and a palpable mass. Using the King's College Hospital classification, 14 patients had type 1 malformations, 8 had type 4 malformations, and 3 had type 2 malformations. Median age at operation was 2 years (range 35 days to 13.5 years). Two centers performed open excision while the third center used primarily a laparoscopic-assisted technique. Median follow-up was 2.1 years (range 30 days to 11.9 years). Three patients (12%) required repeat laparotomy. The wound infection rate was 8% (n = 2). The recurrent cholangitis rate was 8% (n = 2). There was one late death due to adhesive small bowel obstruction, 4 years after surgery. To date, no patient has developed biliary tree stones or liver failure.Conclusions Choledochal malformation excisional surgery, either open or laparoscopic assisted, can be safely performed in appropriately equipped, pediatric surgical centers in Scotland by experienced pediatric surgeons.
Keywords: choledochal malformation; surgery; laparoscopic